Predicting weaning failure in critically ill older patients: secondary analysis of a national multicenter prospective cohort in Turkiye - Kasapoglu, Umut Sabri; Yazicioglu Mocin, Ozlem; Tuncay, Eylem; Gungor, Sinem; Arikan, Huseyin; Ediboglu, Ozlem; Kurtulus, Serif (Bmc, 2026)
Background Traditional predictors of weaning outcomes primarily focus on acute illness severity and physiological parameters, while geriatric vulnerability domains such as frailty, functional dependence, and nutritional risk are often overlooked. Evidence regarding the incremental prognostic value of these domains for predicting weaning failure in critically ill older patients remains limited.This study aimed to evaluate the association between pre-admission frailty, functional status, comorbidity burden, and acute organ dysfunction with weaning failure in critically ill patients aged >= 65 years, and to compare their prognostic contribution with traditional severity scores. Methods This study is a secondary analysis of a national, multicenter, prospective observational cohort conducted across adult ICUs in T & uuml;rkiye. Consecutive ICU patients aged >= 65 years who required invasive mechanical ventilation for more than 24 h were included. Multivariable logistic regression was used to identify factors independently associated with weaning failure. Weaning failure was defined as the need for reintubation within 7 days after extubation, death during the weaning process, or persistent requirement for invasive mechanical ventilation at day 90. Model discrimination was assessed using the area under the receiver operating characteristic curve (AUC). Results A total of 647 critically ill older patients were included in the study. Weaning failure occurred in 347 patients (53.6%). There was no significant difference in age between patients with weaning failure and those successfully weaned. Patients with weaning failure had significantly higher frailty scores, greater comorbidity burden, more severe organ dysfunction, higher nutritional risk, and worse functional dependency. In the final multivariable logistic regression model, higher Clinical Frailty Scale (CFS) (aOR = 1.26 per point; 95% CI = 1.16-1.38) and higher Sequential Organ Failure Assessment (SOFA) score (aOR = 1.12 per point; 95% CI = 1.06-1.19) were independently associated with weaning failure. Conclusions In critically ill older patients, frailty and early organ dysfunction were the factors most strongly associated with weaning failure, whereas chronological age alone showed limited prognostic value, supporting a shift from age-based to vulnerability-based risk assessment
Keywords: Weaning Failure; Older Patients; Frailty; Mechanical Ventilation; Intensive Care Unit; Prognosis